Imparting gestalt essence in identifying user preferences towards interior design / Nur Syatirah Othman, Mohd Nizam Osman and Nor Arzami Othman - Othman, Nur Syatirah; Osman, Mohd Nizam; Othman, Nor Arzami (UiTM Cawangan Perlis, 2020)
behavior and preferences in interior design. Alessi and Trollip Instructional Design Model has been utilized as a methodology in this study which consist of planning, design and development. Heuristic Evaluation and User Acceptance Test has been applied in completing this experiment. Three multimedia experts have been selected to identify usability problems that occur in the user interface (UI) design. After the refinement was made to the application, the User Acceptance Test was conducted to the user. A total of 60 participants at random selected as a target user to participate in this study. The results demonstrate this multimedia application is effective in satisfying the user needs and demand of the decoration of their dream house. Thus, the researcher was able to identify user behavior and preferences in interior design. With three dimensional (3D) features that were applied in this multimedia application, it helps the user to feel more self-assured with their interior design. At the end of this research, the developments of this application bring numerous benefits for both parties either the users or the developer in many aspects. Thus, the society will be disclosing to the use of technology in the interior design in this sophisticated era.